Sex differences in the hypothalamic–pituitary–adrenal axis: An obstacle to antidepressant drug development?. (26th June 2019) - Kokras, Nikolaos; Hodes, Georgia E.; Bangasser, Debra A.; Dalla, Christina
Abstract : Hypothalamic–pituitary–adrenal (HPA) axis dysfunction has long been implicated in the pathophysiology of depression, and HPA axis‐based compounds have served as potential new therapeutic targets, but with no success. This review details sex differences from animal and human studies in the function of HPA axis elements (glucocorticoids, corticotropin releasing factor, and vasopressin) and related compounds tested as candidate antidepressants. We propose that sex differences contribute to the failure of novel HPA axis‐based drugs in clinical trials. Compounds studied preclinically in males were tested in clinical trials that recruited more, if not exclusively, women, and did not control, but rather adjusted, for potential sex differences. Indeed, clinical trials of antidepressants are usually not stratified by sex or other important factors, although preclinical and epidemiological data support such stratification. In conclusion, we suggest that clinical testing of HPA axis‐related compounds creates an opportunity for targeted, personalized antidepressant treatments based on sex. LINKED ARTICLES: This article is part of a themed section on The Importance of Sex Differences in Pharmacology Research. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v176.21/issuetoc